Kontribusi Pembelajaran Discovery Dan DemonstrasiTerhadap Hasil Belajar Ilmu Pengetahuan AlamDitinjau Dari Motivasi Belajar Siswa(Eksperimen Pada Sekolah Dasar Negeri Gugus II Kecamatan Banjarsari) - Pujirahayu, Dwi (2015)
Contribution Discovery Learning and Demonstration on Science Learning outcomes in terms of student motivation. Thesis. Surakarta: Master of administration Education Graduate Program, University of Muhammadiyah Surakarta, September 2015. This study aims to determine: (1) Contribution discovery learning and the demonstration against science learning outcomes in terms of student motivation. (2) Differences Contributions high and low motivation to learn science results. (3) Interaction contribution discovery learning and demonstrations against the results of science learning. This study will be conducted in SDN Bromantakan No. 56 Surakarta and SDN Bibiskalang No. 46 Surakarta in the second semester of the academic year 2014/2015, ie from February to July 2015. The method used is an experimental method to design 2 X 2 factorial design study population are students of class V. The sampling technique used was purposive random sampling. These samples included 80 students. The instrument used for data collection in the form of test results in the form of multiple-choice learning and motivation questionnaire. To determine the validity and regularity achievement test conducted tests for validity and reliability. Validity used is content validity and validity of items. To measure the validity of test items used formula of Pearson Product Moment correlation and reliability used formulas Shopping Two of Spearman Brown. As for the validity of the measure motivation questionnaire used formula of Pearson Product Moment Correlation, and reliability are used Cronbach alpha formula. The analysis technique used is the Analysis of Variance (ANAVA) and Tukey test continued at significance level α = 0.05. Achievement test data show that: (1) There is a positive contribution to the learning discovery and demonstration of learning outcomes Natural Sciences (FA> F table, namely 4.965> 3.970). (2) There are differences in the contribution of the Natural Sciences learning among students who have learning motivation high, medium, and low (FB > table, ie 3.583 > 3.120). (3) There is no interaction effects contribute learning (discovery and demonstration) and motivation towards learning outcomes Natural Sciences (FAB <F table, ie 0.419 <3.120). Results of this study concluded that the discovery and demonstration of learning contribute positively to the learning outcomes of Natural Sciences. Student motivation will affect the learning outcomes of Natural Sciences. There is no interaction effect between the contribution of learning (discovery and demonstration) and motivation towards learning outcomes Natural Sciences.